Dissimilaridade genética de girassol por meio de caracteres quantitativos - Gonsiorkiewicz Rigon, Joao Paulo [UNESP]; Capuani, Silvia [UNESP]; Cherubin, Mauricio Roberto; da Rosa, Genesio Mario; Wastowski, Arci Dirceu (Universidade Federal de Santa Maria (UFSM), 2012)
The aim of this study to evaluate by means of quantitative traits, the genetic dissimilarity among sunflower cultivars in different locations, in addition to the agreement between the methods in order to extract lines for future crosses. There were eight sunflower hybrids grown in two locations in northwestern Rio Grande do Sul, mainly with soil type Oxisol. Multivariate methods were used to determine the genetic diversity, using the Mahalanobis distance. Although the different yield between locations and cultivars, methods of grouping agreed among them selves. To obtain segregating populations, regardless of location, the cultivate 'Olisun 5', demonstrated greater potential for hybridization, with major contributions through number of achenes per chapter and height of the insertion section.
Agronomic performance and genetic dissimilarity sunflower
Keywords: genetic divergence; Helianthus annuus; cluster